Isolation and identification of endophytic fungus in controlling sheath blight disease caused by rhizoctonia solani / Muhammad Faizul Che Hassan - Che Hassan, Muhammad Faizul (Faculty of Plantation and Agrotechnology, 2019)
In Malaysia, rice had become the third major crop for agricultural diversification. Rice production was decreased by the infection of the fungal diseases and sheath blight disease caused by Rhizoctonia solani identified as one of the major disease problems that giving most economical serious issue among paddy sector in Malaysia. Sheath blight disease of paddy in agriculture was commonly produced from fungus Rhizoctonia solani or Rhizoctonia solani khun. Previously, the management of sheath blight disease was relied on chemical fungicides and became the most common method in controlling the disease among smallholders and local farmers. However, chemical controls by fungicides caused adverse effects on the environment and human health. Therefore, the use of endophytic fungi as biological control against sheath blight disease on paddy was considered as a potential non-chemical means and environmental friendly. The objectives of this study were to isolate the endophytic fungi from healthy rice and to identify the effectiveness of endophytic fungus against sheath blight disease on paddy. Four isolates of endophytic fungi evaluated for their antagonistic activity against Rhizoctonia solani under in-vitro conditions. However, all isolates obtained which identified as Fusarium spp. were generally unsuccessful in controlling sheath blight disease. It showed the negative result which all isolates failed to retard the pathogen’s growth on the PDA medium.